Analisis Kandungan Kalsium Karbonat (CaCO3) Batu Gamping Di Kelurahan Bontoa Kecamatan Minasate’ne Kabupaten Pangkajene Dan Kepulauan - Ayu Annisa Amir; Muh. Said L.; Ayusari Wahyuni; Rahmaniah (Universitas Islam Negeri Alauddin Makassar, 2022)
The research had been carried out with the aim of finding out and analyzing the quality of the calcium carbonate content (CaCO3) of limestone as a raw material for making marble. To determine the CaCO3 content, the method was using gravimetric method by weighing empty beaker mass parameter, and the mass of sample and beaker plus HCl 2N level as the final mass after the reaction. The used sample consist of two blocks, they were block one on the coordinate point of 4º48’-4º51’ LS and 119º35’-119º37’ BT and block two on the coordinate point of 4º47’-4º51’ LS and 119º37’-119º39’ BT. The sampling technique was using a chisel and hammer. The result of the research shows that the average of CaCO3 content at the two sampling points was obtained each of 85,530 % and 84,6897%. It is obtained that the level of CaCO3 in the limestone meets the Standar Industri Indonesia (SII) requirement, which is above 50% and it means that the sampling point in Bontoa village, Minasate’ne district, Pangkajene Regency and Island able to be used as marble raw material.